THE DEVELOPMENT OF TEACHING MATERIALS BASED ON LOCAL WISDOM IN JIGSAW LEARNING MODEL FOR DESCRIPTION WRITING SKILLS - Krisna Anggraeni; Devi Afriyuni Yonanda (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
This study aims to find out how to design a teaching materials based on local wisdom in jigsaw learning model for description writing skills. The research method used are“The Research and Development Method of Borg & Gall”. The teaching materials develop six learning meetings based on the analysis of elementary school studentsneed in grade IV in Indramayu. The validation of teaching material product design was carried out by four expert teams as validators which produced a score of 86.45% with very good assessment criteria. The readability of the book test results by students obtained a score of 89. The results of the product trials obtained very good criteria, the practicality response of teachers 91.67% and the practicality response of students 86.57%. The conclusion is, the teaching materials based on local wisdom in jigsaw learning model for description writing skills are valid and practical to use.